JUVENILE DELINQUENCY: CAUSES, LEGAL ANALYSIS, AND PREVENTIVE MEASURES - Buriyev Qobilovich, Odil; Dilshodbek Komilovich, Normatov (Journal of Learning on History and Social Sciences, 2025)
Objective: This study aims to analyze the underlying causes of juvenile delinquency, assess the effectiveness of legal frameworks in addressing youth crime, and explore preventive measures that integrate legal, educational, and social support systems. Method: The research employs a qualitative approach, utilizing legal analysis, case studies, and a review of existing literature on juvenile justice systems. A comparative analysis of different legal frameworks provides insights into the effectiveness of punitive versus rehabilitative approaches. Results: The findings reveal that juvenile delinquency is predominantly influenced by socio-economic disparities, family dysfunction, and gaps in the education system. Legal interventions focusing solely on punishment are often insufficient in reducing recidivism. Instead, a comprehensive approach incorporating legal reform, educational policies, and community-based interventions proves more effective in preventing youth crime. Novelty: This study contributes to the discourse on juvenile justice by emphasizing the integration of preventive legal policies with educational and social support mechanisms. Unlike previous studies that focus primarily on punitive measures, this research highlights a multidisciplinary approach as a sustainable solution for reducing juvenile delinquency.